A Review: Farmers' Local Wisdom on Natural Resources - Zuhud Rozaki; Oki Wijaya; Khamsing Keothoumma; Emil Salim (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2020)
Natural resources are essential parts of human life, even the technologies continue to grow, natural resources still become a strategic sector for many countries. Many countries that don’t have many natural resources are trying to collaborate with rich countries. How people manage natural resources is very important to get maximum benefits. Local wisdom seems to have a role in managing natural resources with wise ways, get full benefits without destroying it. Natural resources, especially in terms of soil, water, plant and animal diversity, vegetation cover, climate, and ecosystem services, are fundamental for agricultural systems' structure and function. Therefore how farmers are managing their farming can be seen as farmers are managing natural resources. Farmers’ local wisdom on natural resources can be seen in the shape of how farmers managing their farming activities with various ways that they learned or got from generation to generation. Understanding farmers’ local wisdom on natural resources can help stakeholders make a suitable program for farmers' lives and natural resources development.